2019
DOI: 10.1128/mcb.00109-19
|View full text |Cite
|
Sign up to set email alerts
|

Myc Regulation of a Mitochondrial Trafficking Network Mediates Tumor Cell Invasion and Metastasis

Abstract: The Myc gene is a universal oncogene that promotes aggressive cancer, but its role in metastasis has remained elusive. Here, we show that Myc transcriptionally controls a gene network of subcellular mitochondrial trafficking that includes the atypical mitochondrial GTPases RHOT1 and RHOT2, the adapter protein TRAK2, the anterograde motor Kif5B, and an effector of mitochondrial fission, Drp1. Interference with this pathway deregulates mitochondrial dynamics, shuts off subcellular organelle movements, and preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 65 publications
0
30
0
1
Order By: Relevance
“…The role of oncogenic Myc [35] in this pathway, which may be responsible for the overexpression of MFF in primary and metastatic tumours, in vivo, fits well with an expanding role of Myc in mitochondrial reprogramming in cancer. In addition to oxidative phosphorylation gene expression [36] and modulation of multiple bioenergetics pathways [37], Myc-directed transcription has been associated with mitochondrial dynamics, promoting changes in organelle structure that favour therapy resistance [38] or heightened subcellular mitochondrial trafficking to fuel tumour cell invasion and metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of oncogenic Myc [35] in this pathway, which may be responsible for the overexpression of MFF in primary and metastatic tumours, in vivo, fits well with an expanding role of Myc in mitochondrial reprogramming in cancer. In addition to oxidative phosphorylation gene expression [36] and modulation of multiple bioenergetics pathways [37], Myc-directed transcription has been associated with mitochondrial dynamics, promoting changes in organelle structure that favour therapy resistance [38] or heightened subcellular mitochondrial trafficking to fuel tumour cell invasion and metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH-1) cells were a gift from Dr. Simon Hayward (Vanderbilt University, Nashville, TN) and primary human foreskin fibroblasts (HFF) were a gift from Dr. Meenhard Herlyn (The Wistar Institute, Philadelphia, PA). Neuroblastoma SHEP21N, SHEP21-NMycER cells containing a conditionally-regulated N-Myc transgene were as described [30] and used in recent studies of mitochondrial reprogramming in cancer [29]. In these cells, treatment with 50 ng/ml doxycycline (Dox) for 48 h suppresses N-Myc expression, whereas addition of 4-hydroxytamoxifen (4OHT, 0.5 μg/ml) results in strong N-Myc induction.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial dynamics was shown to be reprogrammed in tumor cells via gathering mitochondria at the cortical cytoskeleton (Caino et al, 2016). The mechanism could power the membrane machinery of cell movements, maintained phosphorylation of cell motility kinases, and heightened tumor invasion, chemotaxis, and metastasis (Caino et al, 2016; Agarwal et al, 2019). Besides, remodeling of mitochondrial functions is considered the commonest modified downstream of MYC gene, due to the MYC-dependent transcriptional control of GTPase RHOT1/RHOT2 and posttranslational modifications, such as RHOT phosphorylation by PINK kinase (Wang et al, 2011; Bailey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour metastasis, a process implicated in 90% of cancer deaths, is also dictated by changes in mitochondrial function and distribution [104]. Agarwal et al [105] demonstrated that the exploitation of mitochondrial trafficking is a key hallmark of myc-driven tumour progression, where subcellular mitochondrial trafficking to the cortical cytoskeleton is vital for tumour cell invasion and metastasis. Myc proteins are products of oncogenes, often amplified in human cancers, which promote tumour growth and progression.…”
Section: Mitochondrial Targeting To Treat Cancermentioning
confidence: 99%
“…Myc proteins are products of oncogenes, often amplified in human cancers, which promote tumour growth and progression. They have been associated with the control of the gene network of mitochondrial trafficking and changes in the expression of OXPHOS genes and bioenergetics pathways [105]. Mitochondrial trafficking and redistribution is a vital and standard process in healthy neurones, where mitochondria are repositioned to axon terminals to fuel highly energy-intensive processes such as synaptic functions and active growth cones [106]; however, the same protein network is exploited by tumour cells to propel metastasis [107].…”
Section: Mitochondrial Targeting To Treat Cancermentioning
confidence: 99%